Management of type 2 diabetes mellitus and feline infectious peritonitis in a Persian Peaknose cat - Nashrullah, Fathul Barry Akbar; Aulia, Anis; Mahdani, Alya Nur; Putri, Marisya Salsabila Maharani; Wira, Dwi Wahyudha; Hanafiah, Septiani Purwanti (ARSHI Veterinary Letters, 2025)
Feline diabetes mellitus (DM) and infectious peritonitis (FIP) are challenging metabolic and infectious diseases in cats that require long-term management and therapeutic strategies. This case report describes the clinical management of a 7-year-old male Persian peaknose cat diagnosed with type 2 DM and non-effusive FIP at the West Java Animal Hospital. The cat presented with polyuria, polydipsia, and severe weight loss over seven days. Hematological findings showed hyperchromic microcytic anemia and elevated MID%, while biochemical analysis indicated hyperglycemia (524 mg/dL), increased ALT, and a low albumin-to-globulin (A/G) ratio (0.6), consistent with type 2 DM and FIP. Treatment included Molnupiravir, Glimepiride as an antihyperglycemic agent; Ornipural for hepatodigestive support; vitamin supplementation (B complex, A, D, and E); and a low-sugar diet. Blood glucose levels monitored daily for seven days showed a progressive decrease but remained above the normal threshold. This case demonstrates the importance of comprehensive management combining causative, symptomatic, and supportive therapies in feline patients with concurrent disorders. This highlights the need for glucose monitoring, nutritional adjustment, and client education regarding insulin therapy to achieve glycemic control in complex feline comorbidities.